Population’s perception of the solutions proposed by the State for socio-environmental conflicts associated with underground coal mines in Criciúma - SC - Corrêa, Rosany; Ruiz, Mauro Silva; Kniess, Cláudia Terezinha; Gallardo, Amarilis Lucia Casteli Figueiredo; Ramos, Heidy Rodriguez (Revista de Administração da UFSM, 2017)
Conflicts are inherent to the human being and when they involve environmental issues multiple stakeholders with conflicting but legitimate interests are involved. This article sought to answer: What is the perception of surface owners as to the actions taken by the state in mediating conflicts of negotiations related to environmental damage caused by surface subsidence of old coal mines? The methodological procedures adopted to answer this question involved bibliographical and documentary research and interviews with actors directly or indirectly involved in the conflicts. Today's conflicts stem from the subsidence of underground mines due to the expansion of the city on the mined areas in the past. As buildings and streets spreaded over the land surface, collapses of old mines started occcurring, opposing the interests of landowners and companies holding mining rights, this way generating conflicts. In conclusion, it was observed that, depending on the interests at stake and the bargaining power of the actors, these conflicts have been resolved via lawsuits in the courts or through negotiation between the two major parties involved.